1970
DOI: 10.5424/sjar/2010083-1273
|View full text |Cite
|
Sign up to set email alerts
|

The effect of moisture content on physical and mechanical

Abstract: The objective of this study was to investigate some physical and mechanical properties of Osmancık-97 rice variety widespread cultivated in Turkey in order to determine needed designing parameters for handling and storage facilities. In this study, some physical and mechanical properties were evaluated as a function of moisture content in the range of 10-14% d.b. Length, width, thickness, arithmetic and geometric mean diameter ranged from 8.27 to 9.01 mm, 3.10 to 3.48 mm, 2.05 to 2.26 mm, 4.47 to 4.92 mm, 3.75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
3
25
0
1
Order By: Relevance
“…where μ is the Poisson's ratio, which can be calculated by the equation of Kibar et al [29] as expressed in Table 1, and E is the Young modulus, which is related to the moisture content by the following equation [30] :…”
Section: Stress-strain Analysismentioning
confidence: 99%
“…where μ is the Poisson's ratio, which can be calculated by the equation of Kibar et al [29] as expressed in Table 1, and E is the Young modulus, which is related to the moisture content by the following equation [30] :…”
Section: Stress-strain Analysismentioning
confidence: 99%
“…To evaluate thousand grain weight (M1,000), randomly selected grains from the bulk were averaged and measured using an electronic balance to an accuracy of 0.01 g (Markowski et al 2013). The grains were then allowed to settle into the container, and the excess was removed before determining the bulk density using the following equation (Kibar et al 2010): The bulk density container was filled to 5 cm above the top.…”
Section: Functional Propertiesmentioning
confidence: 99%
“…The static coefficient of friction was calculated from the constant friction strength through the digital dynamometer after movement (Kibar et al 2010), with three replications performed. During the experiment, the test surface moved at low velocity (2.2 cm/s).…”
Section: Functional Propertiesmentioning
confidence: 99%
“…Carman (1996), Gupta and Das (1997), Kibar et al (2010), Visvanathan et al (1996) and Aviara et al (2014a) found the bulk density of lentil (Lens culinaris) seeds, sunflower seeds, Mucuna flagellipes nuts, rice (Oryza sp.) seeds, neem (Azadirachta indica) nuts, and Brachystegia eurycoma seeds, respectively, decreased as the seed moisture content increased.…”
Section: Bulk Densitymentioning
confidence: 99%